2014
DOI: 10.1016/j.ydbio.2013.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Pax3 and Zic1 trigger the early neural crest gene regulatory network by the direct activation of multiple key neural crest specifiers

Abstract: Neural crest development is orchestrated by a complex and still poorly understood gene regulatory network. Premigratory neural crest is induced at the lateral border of the neural plate by the combined action of signaling molecules and transcription factors such as AP2, Gbx2, Pax3 and Zic1. Among them, Pax3 and Zic1 are both necessary and sufficient to trigger a complete neural crest developmental program. However, their gene targets in the neural crest regulatory network remain unknown. Here, through a transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
104
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 67 publications
(87 reference statements)
10
104
0
Order By: Relevance
“…Moreover, Pax3/7 and Msx1 are also required for the expression of Ets1 (Barembaum and Bronner, 2013), highlighting their importance during the early steps of neural crest specification. Similarly, Pax3/7 has also been shown to cooperate with Zic1 to drive neural crest specification in frog embryos (Bae et al, 2014;Plouhinec et al, 2014). In X. laevis, for example, Zic1 together with Pax3/7 (Milet et al, 2013) bind directly to the Snai1 and Snai2 promoters (Plouhinec et al, 2014).…”
Section: Induction and Formation Of The Neural Plate Bordermentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Pax3/7 and Msx1 are also required for the expression of Ets1 (Barembaum and Bronner, 2013), highlighting their importance during the early steps of neural crest specification. Similarly, Pax3/7 has also been shown to cooperate with Zic1 to drive neural crest specification in frog embryos (Bae et al, 2014;Plouhinec et al, 2014). In X. laevis, for example, Zic1 together with Pax3/7 (Milet et al, 2013) bind directly to the Snai1 and Snai2 promoters (Plouhinec et al, 2014).…”
Section: Induction and Formation Of The Neural Plate Bordermentioning
confidence: 99%
“…Similarly, Pax3/7 has also been shown to cooperate with Zic1 to drive neural crest specification in frog embryos (Bae et al, 2014;Plouhinec et al, 2014). In X. laevis, for example, Zic1 together with Pax3/7 (Milet et al, 2013) bind directly to the Snai1 and Snai2 promoters (Plouhinec et al, 2014). They also directly regulate FoxD3 expression in the chick trunk neural crest (Simoes-Costa et al, 2014).…”
Section: Induction and Formation Of The Neural Plate Bordermentioning
confidence: 99%
“…The combined activity of these major signaling pathways induces the expression of transcription factors including Gbx2, Dlx, Msx1 and Msx2, Pax3 and Pax7, Ap2alpha (also known as Tfap2a), and Zic1 (Brewer et al, 2004;Khadka et al, 2006;Li et al, 2009;Luo et al, 2003Luo et al, , 2001Monsoro-Burq et al, 2005;Plouhinec et al, 2014;Woda et al, 2003) in an area between neural and non-neural ectoderm. These factors cooperatively define the neural plate border (NPB) and interact to induce expression of neural crest specific genes.…”
Section: Introductionmentioning
confidence: 99%
“…During vertebrate gastrulation and neurulation, the dorsal ectoderm is patterned into several cell fates: neural plate (NP), non-neural ectoderm (NNE), neural crest (NC) and preplacodal ectoderm (P), a prerequisite for the differentiation of the central and peripheral nervous systems and surrounding tissues. Focusing on genes enriched dorsally during neurulation 9,12 , we found that : non-neural ectoderm (NNE), neural plate (NP), neural border (NB), preplacodal ectoderm (P) and blastopore (Blastp). In late gastrulas, pfkfb4 is expressed broadly dorsally, encompassing sox2 pan-neural expression.…”
mentioning
confidence: 99%